Classical radical hysterectomy and nerve-sparing radical hysterectomy in the treatment of cervical cancer - Makowski, Marcin; Nowak, Marek; Szpakowski, Marian; Władziński, Jacek; Serwach-Nowińska, Anna; Janas, Łukasz; R. Wilczyński, Jacek (Menopause Review/Przegląd Menopauzalny, 2014)
Aim of the study: To compare Piver III radical hysterectomy (RH) with nerve-sparing radical hysterectomy (NSRH) for cervical cancer patients in terms of postoperative physiology of pelvic autonomic nerves and perioperative complications. Material and methods : Seventy-three consecutive patients with invasive cervical cancer underwent RH (53 cases) or NSRH (20 cases) from 2001 to 2012 at the Department of Gynecology and Gynecologic Oncology of Polish Mother’s Memorial Hospital – Research Institute in Łódź. Results : Compared with patients treated with RH, patients who underwent NSRH presented no significant difference in terms of operative time (146 vs. 143 minutes, p > 0.05), blood loss and hospital stay (9.2 vs. 7.5 days, p > 0.05). A positive surgical margin was found in 6 cases of RH. No serious surgical complications were found in the NSRH group, while there were 4 cases in the RH group. Conclusions : Nerve-sparing radical hysterectomy is safe and feasible surgical management for cervical cancer patients, which should improve the physiology of the pelvic autonomic nerve system postoperatively. The technique is relatively new and its oncologic efficiency has not been fully established yet, moreover it requires sophisticated anatomical knowledge and high operative skills.